Oxidative potential determines the oxidative stress and ferroptotic toxicity of airborne particulate matter on pulmonary epithelial cells - Bingxue Nie; Daoqiang Zhang; Xin Liu; Chengying Lei; Zhiruo Li; Nan Zhang; Shuping Zhang; Yiju Wei; Jie Zhang (Ecotoxicology and Environmental Safety, 2025)
Exposure to airborne particulate matter (PM) is a major risk which increases pulmonary diseases such as asthma, chronic bronchitis, or chronic obstructive pulmonary disease (COPD). PM is a complex mixture with physiochemical properties that can vary over time and space, presenting a challenge when attempting to analyze their health risks. In this study, we compared two kinds of commercial PM with real PM to explore an index which takes account of both the diverse physicochemical properties of PM and accurate prediction of their toxicities. Our results indicated that the oxidative potential (OP) of PM significantly affects their cytotoxicity. In comparison to two kinds of commercial PM such as carbon black and SRM-1648a, real ambient PM2.5 induced more significant oxidative stress and ferroptosis, which was closely associated with its higher OP. Notably, the use of radical scavengers like vitamin C and coumarin decreased the OP of PM2.5 effectively, thereby leading to a decrease in its cytotoxic effects. Furthermore, the reduction of OP reversed redox imbalance and alleviated lung damage in vivo. This study provides additional insights into the structure-activity relationship for PM’s toxicity. It also sheds light on further investigations on the detoxication of PM.